Heart rate-lowering therapy in gout patients with stable coronary artery disease: focus on ivabradine - N. N. Kushnarenko; T. A. Medvedeva; M. Yu. Mishko; T. M. Karavaeva (Российский кардиологический журнал)
Aim. To study the effect of ivabradine and bisoprolol on cardiac hemodynamics and diastolic remodeling in gout patients with coronary artery disease and hypertension and without left ventricular systolic dysfunction.Material and methods. The open randomized parallel clinical trial of 35 men with intercritical gout at the age of 41,4±3,3 years, with class II-III stable angina, hypertension and sinus rhythm without data suggestive of heart failure was performed. All patients included in the study were randomly divided into two groups: eighteen patients took bisoprolol at a dose of 2,5 to 10 mg/day, 17 subjects received bisoprolol 2,5 mg/day with ivabradine (Coraxan, SERVIER, France) 5 mg 2 times a day. Adjustment of the therapy was carried out every 2 weeks until the target heart rate (HR) was reached at 55-60 beats/min and then remained unchanged until 12 weeks of therapy. All patients underwent echocardiography, 24-hour Holter and central aortic blood pressure monitoring, and 3-minute cycle ergometer test with a power of 25, 50, 75 and 100 watts.Results. There was a comparable decrease in the maximum and minimum 24-hour average heart rates in patients receiving only bisoprolol and those taking bisoprolol+ivabradine. Patients taking bisoprolol+ivabradine had a decrease of central systolic and diastolic blood pressure (BP). Pulse pressure in the bisoprolol group increased by 17,7% (p=0,02), and when ivabradine was added, on the contrary, it decreased by 7,0% (p=0,04). Twelve-week therapy with beta-blockers and ivabradine was accompanied by an effective decrease in the pulse wave velocity in both groups (p<0,05). All gout patients did not have a decrease of systolic function and there was an improvement in diastolic remodeling with beta-blockers and ivabradine therapy.Conclusion. The results obtained indicate that the addition of ivabradine to bisoprolol leads to an effective decrease in heart rate, an improvement in arterial stiffness and exercise tolerance. Combination therapy with ivabradine is accompanied by an improvement in clinical outcomes using lower doses of bet-blockers, which requires further study and a double-blind controlled study.